Evaluation of the aorta in infants with simple or complex coarctation of the aorta using CT angiography - Xiao, Hui-Jun; Zhan, A-Lai; Huang, Qing-Wen; Huang, Rui-Gang; Lin, Wei-Hua (Frontiers in Cardiovascular Medicine, 2023)
Objective To assess aortic dilatation and determine its related factors in infants with coarctation of the aorta (CoA) by using computed tomography angiography (CTA). Methods The clinical data of 55 infantile patients with CoA diagnosed by CTA were analyzed retrospectively. Aortic diameters were measured at six different levels and standardized as Z scores based on the square root of body surface area. The results of simple and complex CoA were compared. Univariate and multivariate logistic regression were used to analyze the effects of sex, age, hypertension, degree of coarctation, CoA type, bicuspid aortic valve (BAV), and other factors related to aortic dilatation. Results In total, 52 infant patients with CoA were analyzed, including 22 cases of simple CoA and 30 cases of complex CoA. The ascending aorta of the infants in the simple CoA group and the complex CoA group were dilated to different degrees, but the difference was not statistically significant (50.00% vs. 73.33%, P = 0.084, and 2.05 ± 0.40 vs. 2.22 ± 0.43 P = 0.143). The infants in the complex CoA group had more aortic arch hypoplasia than those in the simple CoA group (33.33% vs. 9.09%, P = 0.042). Compared to the ventricular septal defect (VSD) group, the Z score of the ascending aorta in the CoA group was significantly higher than that in the VSD group (P = 0.023 and P = 0.000). A logistic retrospective analysis found that an increased degree of coarctation (CDR value) was an independent predictor of ascending aortic dilatation (adjusted OR = 0.002; P = 0.034). Conclusion Infants with simple or complex CoA are at risk of ascending aortic dilatation, and the factors of ascending aortic dilatation depend on the degree of coarctation. The risk of aortic dilatation in infants with CoA can be identified by CTA.